2018
DOI: 10.1007/s12026-018-8993-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor gene polymorphisms are associated with systemic lupus erythematosus susceptibility or lupus nephritis in Mexican patients

Abstract: The TNF -238G/A (rs361525) and -308G/A (rs1800629) polymorphisms have consistently been associated with systemic lupus erythematosus (SLE) in several populations; however, these findings have not been verified in all populations. Here, we aimed to examine whether the TNF -238G/A, -308G/A, -376G/A (rs1800750), and -1031T/C (rs1799964) polymorphisms confer SLE or lupus nephritis (LN) susceptibility in a Mexican population. Our study included 442 patients with SLE and 495 controls. For genotyping, we used the Taq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Genetic studies have revealed that gene polymorphisms of TNF-α are risk factors for the development of nephrotic syndrome among Egyptian children and are linked with steroid resistance [79]. Additionally, some TNF gene polymorphisms in Mexican patients were associated with systemic lupus erythematosus (SLE) and lupus nephritis [80].…”
Section: Tumor Necrosis Factormentioning
confidence: 99%
“…Genetic studies have revealed that gene polymorphisms of TNF-α are risk factors for the development of nephrotic syndrome among Egyptian children and are linked with steroid resistance [79]. Additionally, some TNF gene polymorphisms in Mexican patients were associated with systemic lupus erythematosus (SLE) and lupus nephritis [80].…”
Section: Tumor Necrosis Factormentioning
confidence: 99%
“…TNF-α is coded and regulated by TNF-α gene, which is located in chromosome 6, within the class III region of MHC (9). Several studies analyzed the association of TNF-α gene with susceptibility to RA and SLE (10 12) and numbers of single-nucleotide polymorphisms (SNPs) of TNF-α gene were identified. Among these, two common polymorphisms in the promoter, G to A substitution at position -238 ( TNF-α-238G/A, rs361525) and position -308 ( TNF-α-308G/A, rs1800629), attracted widespread attention.…”
Section: Introductionmentioning
confidence: 99%
“…Models have been developed to confirm the susceptibility conferred by genes in the MHC III region (non-classical HLA and non-HLA genes) linked to HLA-B and -DRB1. The most important linked genes using HLA-DRB1 ∗ 03:01 as covariant are: the proto-oncogene Notch homologue 4 (NOTCH4), the MHC class I polypeptide–related sequence A and B (MIC-A and MIC-B), the steroid 21-hydroxylase (CYP21A2), ( Partanen et al, 1988 ; Morris et al, 2012 ) the three 70 kDa heat-shock proteins (HSPA1A, HSPA1B, HSPA1L), ( Mišunová et al, 2017 ), natural cytotoxicity triggering receptor 3 (NCR3); nuclear factor kappa light chain gene enhancer in B cells inhibitor-like 1 (NFKBIL1), allograft inflammatory factor 1 (AIF1) ( Dorak et al, 2006 ); and the three Tumor Necrosis Factor genes (Lymphotoxin-beta, Lymphotoxin-alpha, and TNF-α) ( Zúñiga et al, 2001 ; Ramírez-Bello et al, 2018 ). Important variants of the genes mentioned above have been deeply studied in Caucasians, and linkage disequilibrium with HLA-B ∗ 08:01 and -DRB1 ∗ 03:01 has been confirmed ( Dorak et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%